Pengaruh Saham Syariah dan Sukuk yang Terdaftar di JII Terhadap Produk Domestik Bruto (PDB) Indonesia Tahun 2015-2019 (Sharia Faculty Islamic Economic Law Study Department, 2021)
The background of this research is a phenomenm of Islamic economic financial which is the instrument of bursary effect. It focuses on the grow sharia stock and sukuk that leads to product domestic bruto (PDB) of certain contry. In this research sharia stock and sukuk as independent variables and product domestic bruto (PDB) as dependent variables. The object of this research is a secondary data from panel data of sharia stock and sukuk from 2015 to 2019. A quantitative method with association approach was chosen as the method of this research and also used doubled linear regression with Eviews 11 programme. The results showed that the sharia stock variables has sig value equal to 0,2409 (p>0,05) in partially, and it mean that it does not affect to the product domestic bruto (PDB) variables. Meanwhile the sukuk variables has sig value equal to 0,000 (p<0,05), and it affect the product domestic bruto (PDB) variables. And in the simultaneously results showed if sharia stock and sukuk variable have sig value equal to 0,000 (p<0,05), it mean affectd the product domestic bruto (PDB) variables. Furthermore through the R Square test (R2), sharia stock and sukuk variables affect 91% of the product domestic bruto (PDB) variables and is 9% affected by other variables that does not included in this research.